2016
DOI: 10.1128/mbio.00755-16
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Cyclic AMP-Dependent Protein Kinase Subunit 3 Is Involved in the Switch from Tachyzoite to Bradyzoite Development

Abstract: Toxoplasma gondii is an obligate intracellular apicomplexan parasite that infects warm-blooded vertebrates, including humans. Asexual reproduction in T. gondii allows it to switch between the rapidly replicating tachyzoite and quiescent bradyzoite life cycle stages. A transient cyclic AMP (cAMP) pulse promotes bradyzoite differentiation, whereas a prolonged elevation of cAMP inhibits this process. We investigated the mechanism(s) by which differential modulation of cAMP exerts a bidirectional effect on parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 34 publications
3
86
0
Order By: Relevance
“…PruΔku80Δhxgprt LDH2-GFP parasites (18) were continuously passaged in human foreskin fibroblast (HFF : ATCC:CRL-1634; Hs27) host cells, as previously described (32). TgIST-KO parasites were obtained as a kind gift from the laboratory of Dr. David Sibley (Washington University School of Medicine, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…PruΔku80Δhxgprt LDH2-GFP parasites (18) were continuously passaged in human foreskin fibroblast (HFF : ATCC:CRL-1634; Hs27) host cells, as previously described (32). TgIST-KO parasites were obtained as a kind gift from the laboratory of Dr. David Sibley (Washington University School of Medicine, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…PKAr typically possesses two cAMP‐binding domains, and the association with cAMP provokes the release of active PKAc that can then phosphorylate downstream targets to propagate cAMP signalling events. In T. gondii , PKAc1 and PKAc2 localise to the parasite periphery whereas PKAc3 is cytosolic (Sugi et al , ) indicating that the spatial control of cAMP levels and PKAc isoforms is crucial to differentially regulate PKA activity. Both PKAc1 and PKAc3 are expressed in tachyzoites and bradyzoites, while PKAc2 is highly expressed during the sexual stages in felids.…”
Section: Introductionmentioning
confidence: 99%
“…Use of H89, an ATP competitive inhibitor showing high affinity for a wide range of PKAc isoforms (Lochner & Moolman, ), previously suggested that PKAc activity is important to regulate the rate of T. gondii division (Kurokawa et al , ) while transient elevation of cAMP by forskolin induced bradyzoite differentiation (Kirkman et al , ). Functional analysis of PKAc3 recently identified this isoform as a key cAMP effector in the regulation of stage conversion between tachyzoites and bradyzoites (Sugi et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the observation that PKA is conserved in apicomplexans [23], two PKAs (SRCN_5610 and SRCN_3990) were identified in S. neurona. In T. gondii , increases in cytosolic cAMP levels activate PKA to trigger the developmental switch from the rapidly proliferating tachyzoites to the quiescent bradyzoites [66]. Additionally, two other S. neurona AGCs (SRCN_5165 and SRCN_3339) were putative PKAs given that they contained the characteristic GxGxxG motif found in PKA [51].…”
Section: Discussionmentioning
confidence: 99%